Molecular Motors and Apical CFTR Traffic in Epithelia - Kravtsov, Dmitri V. (Molecular Diversity Preservation International (MDPI), 2013)
Intracellular protein traffic plays an important role in the regulation of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) chloride channels. Microtubule and actin-based motor proteins direct CFTR movement along trafficking pathways. As shown for other regulatory proteins such as adaptors, the involvement of protein motors in CFTR traffic is cell-type specific. Understanding motor specificity provides insight into the biology of the channel and opens opportunity for discovery of organ-specific drug targets for treating CFTR-mediated diseases.